The Relationship of Knowledge with Anemia Prevention Attitudes in Pregnant Women at Kereng Bangkirai Public Health Centre - Cathryne, Joice; Pertiwi, Elvina Agus; Pandia, Margareth Kristin Br; Renatha, Silvina; Debby, Chryest (MAHESA : Malahayati Health Student Journal, 2024)
ABSTRACT Anemia is a disorder characterized by low hemoglobin levels in the blood. If it affects pregnant women, it can result in severe bleeding and even death during childbirth. In Indonesia, the number of pregnant women dying from anemia increased by 62.6% in 2020–2021. According to midwives at Palangka Raya City's Kereng Bangkirai Public Health Center, 86 pregnant women suffered from anemia in 2021. The purpose of this study to determine the relationship between knowledge and attitude to prevent anemia in pregnant women. This study used a quantitative correlational method with cross-sectional. The sample of this study is 50 first-trimester pregnant women who are registered at the Kereng Bangkirai Public Health Center in Palangka Raya City with accidental sampling as the sampling method. The instrument of this study uses a questionnaire on the knowledge and attitude to prevent anemia among pregnant women. The research was conducted in February-April 2023.   The results showed that 25 (50%) pregnant women had good knowledge, which is 20 (20%) pregnant women had a positive anemia prevention attitude, and 5 (10%) pregnant women had a negative anemia prevention attitude. There was a relationship between knowledge and attitudes toward preventing anemia, as evidenced by the chi-square test results (p=0.047). A good level of knowledge can produce a positive attitude toward anemia prevention in pregnant women. Keywords: Anemia, Attitude, Pregnancy, Pregnant Women